Rhodanthpyrone A and B play an anti-inflammatory role by suppressing the nuclear factor-κB pathway in macrophages - Kim, Kyeong Su; Han, Chang Yeob; Han, Young Taek; Bae, Eun Ju (The Korean journal of physiology & pharmacology, 2019)
Macrophage-associated inflammation is crucial for the pathogenesis of diverse diseases including metabolic disorders. Rhodanthpyrone (Rho) is an active component of Gentiana rhodantha, which has been used in traditional Chinese medicine to treat inflammation. Although synthesis procedures of RhoA and RhoB were reported, the biological effects of the specific compounds have never been explored. In this study, the anti-inflammatory activity and mechanisms of action of RhoA and RhoB were studied in lipopolysaccharide (LPS)-stimulated macrophages. Pretreatment with RhoA and RhoB decreased inducible nitric oxide synthase and cyclooxygenase-2 expressions in RAW 264.7 cells and in thioglycollate-elicited mouse peritoneal macrophages. In addition, it downregulated transcript levels of several inflammatory genes in LPS-stimulated RAW 264.7 cells, including inflammatory cytokines/chemokines (Tnfa, Il6, and Ccl2) and inflammatory mediators (Nos2 and Ptgs2). Macrophage chemotaxis was also inhibited by treatment with the compounds. Mechanistic studies revealed that RhoA and RhoB suppressed the nuclear factor (NF)-κB pathway, but not the canonical mitogen activated protein kinase pathway, in LPS-stimulated condition. Moreover, the inhibitory effect of RhoA and RhoB on inflammatory gene expressions was attenuated by treatment with an NF-κB inhibitor. Our findings suggest that RhoA and RhoB play an anti-inflammatory role at least in part by suppressing the NF-κB pathway during macrophage-mediated inflammation.Macrophage-associated inflammation is crucial for the pathogenesis of diverse diseases including metabolic disorders. Rhodanthpyrone (Rho) is an active component of Gentiana rhodantha, which has been used in traditional Chinese medicine to treat inflammation. Although synthesis procedures of RhoA and RhoB were reported, the biological effects of the specific compounds have never been explored. In this study, the anti-inflammatory activity and mechanisms of action of RhoA and RhoB were studied in lipopolysaccharide (LPS)-stimulated macrophages. Pretreatment with RhoA and RhoB decreased inducible nitric oxide synthase and cyclooxygenase-2 expressions in RAW 264.7 cells and in thioglycollate-elicited mouse peritoneal macrophages. In addition, it downregulated transcript levels of several inflammatory genes in LPS-stimulated RAW 264.7 cells, including inflammatory cytokines/chemokines (Tnfa, Il6, and Ccl2) and inflammatory mediators (Nos2 and Ptgs2). Macrophage chemotaxis was also inhibited by treatment with the compounds. Mechanistic studies revealed that RhoA and RhoB suppressed the nuclear factor (NF)-κB pathway, but not the canonical mitogen activated protein kinase pathway, in LPS-stimulated condition. Moreover, the inhibitory effect of RhoA and RhoB on inflammatory gene expressions was attenuated by treatment with an NF-κB inhibitor. Our findings suggest that RhoA and RhoB play an anti-inflammatory role at least in part by suppressing the NF-κB pathway during macrophage-mediated inflammation.